Pengaruh Book-Tax Differences Dan Tingkat Hutang Terhadap Persistensi Laba(Studi Empiris pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia 2010-2012) - Ayu Kusuma Dewi, Citra, Drs. Muhammad Abdul Aris, M.Si (2015)
This research is aims to examine and find out the empirical of the difference between accounting profit with taxable profit (book-tax differences) and the level of debt on earnings persistence. Sample used in this research are banking companies listed in Indonesian Stock Exchange from 2010 until 2012. Total samples are 26 companies with non- probability sampling method collected using purposive sampling. The method of data analysis is multiple linear regression. Besides, this research is also using simple linear regression to looking for the earnings persistence on this data. The process is using SPSS17.0 software for test. Based on the analysist it was found that the greater the differnce between accounting income with taxable profit (large negative book-tax differences ) showed earnings persistence not low, while the greater difference between accouting income with taxable profit (large positive book-tax differences) showed earnings persistence is also not low. Companies with large negative book-tax differences not shown to have lower persistence than firms with small book-tax differences, while companies with proven large positive book-tax differences have lower earnings persistence than firms with small book-tax differnces. The level of debt is not significant effect on earnings persistence.